Study on the effect of bionic flap based on owl wing contour on aerodynamic noise of airfoil - Xian Fan Xie; Liu Chen; Jian Shen Zhu (Center of Biomass & Renewable Energy (CBIORE), 2026)
Modifying flap geometry to reduce trailing-edge turbulence is an effective approach to lower wind-turbine blade aerodynamic noise. Based on the NACA0018 airfoil, a new bionic serrated flap was designed by mimicking the owl wing structure. Numerical methods were employed to investigate its noise reduction mechanism, utilizing Improved Delayed Detached Eddy Simulation (IDDES) and the Ffowcs Williams-Hawkings (FW-H) method. The aerodynamic and aeroacoustic performance of the baseline airfoil, a flat-plate Gurney flap (PGF), a standard serrated flap (SGF), and the bionic flap (BGF) were calculated at different inflow wind speeds (Re = 7×104, 1.4×105 and 2.1×105) under various inflow angles (0°, 6°, 10° and 15°). Numerical results demonstrate that the proposed BGF configuration mitigates the additional noise induced by the traditional Gurney flap, with reductions observed in the overall sound pressure levels across the monitored directivity points. Compared to the baseline airfoil, the BGF demonstrates noise reduction at low angles of attack (AoA < 6°), with a peak OASPL decrease of 4.6 dB. However, this aeroacoustic advantage diminishes rapidly as the AoA exceeds 6°, suggesting that the noise-suppression effectiveness of the bionic contour is highly sensitive to the inflow angle. Analysis of wake vortex structures and turbulence intensity reveals that the curved bionic flap effectively suppresses vortex clusters and turbulence intensity, leading to reduce the airfoil's aerodynamic noise.